2013
DOI: 10.1111/nph.12448
|View full text |Cite
|
Sign up to set email alerts
|

Age, allocation and availability of nonstructural carbon in mature red maple trees

Abstract: SummaryThe allocation of nonstructural carbon (NSC) to growth, metabolism and storage remains poorly understood, but is critical for the prediction of stress tolerance and mortality.We used the radiocarbon ( 14 C) 'bomb spike' as a tracer of substrate and age of carbon in stemwood NSC, CO 2 emitted by stems, tree ring cellulose and stump sprouts regenerated following harvesting in mature red maple trees. We addressed the following questions: which factors influence the age of stemwood NSC?; to what extent is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
179
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(186 citation statements)
references
References 55 publications
5
179
1
1
Order By: Relevance
“…The ages of sugar and starch were similar, implying regular interconversion between these compounds. Similar results were found in Acer rubrum L., where NSC age increased with the age of the tree; however, comparatively younger NSC was found in more vigorous trees (12). Ten-year-old NSC was allocated to new root growth following a major hurricane disturbance in a dry tropical forest (139), red maple stump sprouts were grown from remobilized NSC in roots as old as 17 years (12), and new roots in desert palms were produced from remobilized NSC as old as >60 years (R. Vargas, C. Czimczik, S. Bullock, X. Xu & S. Djuricin, unpublished data).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The ages of sugar and starch were similar, implying regular interconversion between these compounds. Similar results were found in Acer rubrum L., where NSC age increased with the age of the tree; however, comparatively younger NSC was found in more vigorous trees (12). Ten-year-old NSC was allocated to new root growth following a major hurricane disturbance in a dry tropical forest (139), red maple stump sprouts were grown from remobilized NSC in roots as old as 17 years (12), and new roots in desert palms were produced from remobilized NSC as old as >60 years (R. Vargas, C. Czimczik, S. Bullock, X. Xu & S. Djuricin, unpublished data).…”
supporting
confidence: 74%
“…Similarly, resprouting requires the use of belowground NSC to rebuild both stem and foliage, and observations suggest that plants are able to draw upon much older NSC reserves to do so than they commonly use for annual growth and maintenance (12). Observations suggest that obligate resprouters are actively storing NSC.…”
Section: Wwwannualreviewsorg • Nonstructural Carbon In Woody Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sapwood NSCs have been analyzed in a number of ecological studies (Hoch et al 2003 ;Sauter and Wellenkamp 1998 ;Ashworth et al 1993 ;Palacio et al 2007 ;Carbone et al 2013 ), providing insights into the size and dynamics of the wood parenchyma carbohydrate pool. In the following sections, we will review the NSC accumulation patterns observed in different tree species and different woody organs and discuss changes in NSC concentration and composition that occur throughout the growing season.…”
Section: The Function Of Ray and Axial Parenchyma In The Storage Of Nmentioning
confidence: 99%
“…NSCs provide an essential buffer against fluctuations in carbon (C) supply and C demand for plants and can be used in various ways, such as supporting plant metabolism, promoting new tissue growth, producing protective compounds or storing C for future use (Chapin et al 1990;Herms and Mattson 1992;Carbone et al 2013;Piper and Fajardo 2014). Allocation of NSC to storage tissues by plants can be either a passive process, when C supply exceeds C demands (Chapin et al 1990), or an active process, when NSC is stored at the expense of growth (Wiley and Helliker 2012).…”
Section: Introductionmentioning
confidence: 99%